2019
DOI: 10.1111/faf.12430
|View full text |Cite
|
Sign up to set email alerts
|

Migrations and movements of Atlantic tarpon revealed by two decades of satellite tagging

Abstract: Understanding large‐scale migratory behaviours, local movement patterns and population connectivity are critical to determining the natural processes and anthropogenic stressors that influence population dynamics and for developing effective conservation plans. Atlantic tarpon occur over a broad geographic range in the Atlantic Ocean where they support valuable subsistence, commercial and recreational fisheries. From 2001 through 2018, we deployed 292 satellite telemetry tags on Atlantic tarpon in coastal wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 77 publications
7
53
0
Order By: Relevance
“…Regardless of the mechanism underpinning the importance of the Mississippi River Delta to tarpon, citizen scientists are clearly part of the conservation solution. Several recent advances in our understanding of tarpon population structure (Guindon et al, 2015), movement and migration (Luo et al, 2020), and nursery habitat use (Wilson, Adams, & Ahrens, 2019) have been facilitated by citizen science efforts, particularly in Florida. For example, tarpon anglers from nine southeastern US states (Texas through Virginia) collected nearly 24,000 tarpon tissue samples in support of a genetic mark-recapture study; 96% of these were collected in F I G U R E 2 (a) The move persistence parameter ( g t ) displayed as a time-series for the state-space model filtered tarpon data, with white and grey name templates indicating fish tagged in Alabama verses Louisiana, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the mechanism underpinning the importance of the Mississippi River Delta to tarpon, citizen scientists are clearly part of the conservation solution. Several recent advances in our understanding of tarpon population structure (Guindon et al, 2015), movement and migration (Luo et al, 2020), and nursery habitat use (Wilson, Adams, & Ahrens, 2019) have been facilitated by citizen science efforts, particularly in Florida. For example, tarpon anglers from nine southeastern US states (Texas through Virginia) collected nearly 24,000 tarpon tissue samples in support of a genetic mark-recapture study; 96% of these were collected in F I G U R E 2 (a) The move persistence parameter ( g t ) displayed as a time-series for the state-space model filtered tarpon data, with white and grey name templates indicating fish tagged in Alabama verses Louisiana, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is identifying when northern Gulf of Mexico tarpon begin their fall migration, and whether or not these fish return to Florida. Notably, of the nearly 300 tarpon tracks reported in Luo et al (2020), no tarpon tagged east of the Mississippi River migrated west of Louisiana, or vice-versa. Unfortunately, our tags detached before we could gain insight into these patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Coastal pelagic and highly migratory fishes tagged near the Yucatan Channel or Straits of Florida (the two immigration/emigration points for the GOM) show highly variable movements, whereas species tagged in the NC and NW GOM appear to have movements restricted to the GOM. For example, Luo et al (2020) studying movements of tarpon, Megalops atlanticus, in the GOM, reported that individuals tagged in the SE GOM near the Straits of Florida showed variable movements between the GOM and United States east coast; whereas other individuals tagged in the western GOM primarily remained in the GOM. Similarly, Hueter et al (2013) tagged 35 whale sharks in waters surrounding the Yucatan Peninsula and reported a variety of movements into the GOM, Caribbean Sea, Straits of Florida, and South Atlantic Ocean.…”
Section: Gom Residencymentioning
confidence: 99%
“…Males reach sexual maturity at about 90 cm and females at 128 cm FL [13,[19][20][21]. Much of our knowledge of tarpon movements and behaviors come from satellite tracking and conventional anchor tag studies conducted in Florida, southeast Atlantic, Gulf of Mexico, and the northwestern Caribbean (e.g., Mexico, Belize, Cuba) [6,7,13,14,22,23]. These studies have focused on large-scale movements (>500 km) of large adult tarpon (>130 cm FL) that support a valuable sport shery.…”
Section: Introductionmentioning
confidence: 99%
“…Tracking the movements and migrations of animals in the aquatic environment provides insight into spatial and temporal patterns of habitat use, trophic interactions, reproductive behavior, and behavioral responses to environmental change [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%